Inovasi Administrasi Publik dalam Menyokong Pengembangan Kurikulum Pesantren di Era Digital: Studi di Yayasan Pondok Pesantren Al-Arif NW Teko - Farhanuddin, Farhanuddin; Mardiyono, Mardiyono; Budiar, Budiar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Religious education, particularly in Islamic boarding schools (pesantren), has become an integral part of societal life in many countries, including Indonesia. However, with the rapid social and technological changes emerging, pesantren need to adapt to remain relevant in providing quality education. This research aims to explore the role of innovation in public administration to support the development of pesantren curricula in the digital era, with a focus on Yayasan Pondok Pesantren Al-Arif NW Teko. The research method employs a qualitative approach with in-depth interviews and participatory observation as data collection techniques. Data analysis is conducted through coding and categorization processes to identify patterns and findings emerging from the data. The results indicate that innovation in public administration can facilitate the development of pesantren curricula by introducing new teaching methods, integrating technology, and enhancing information accessibility. The implication emphasizes the importance of collaboration between the government, educational institutions, and society in designing policies that support innovation in religious education.